If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + -2 + x + -4 + x + -6 = 0 Reorder the terms: -2 + -4 + -6 + x + x + x + x = 0 Combine like terms: -2 + -4 = -6 -6 + -6 + x + x + x + x = 0 Combine like terms: -6 + -6 = -12 -12 + x + x + x + x = 0 Combine like terms: x + x = 2x -12 + 2x + x + x = 0 Combine like terms: 2x + x = 3x -12 + 3x + x = 0 Combine like terms: 3x + x = 4x -12 + 4x = 0 Solving -12 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4x = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = 0 + 12 4x = 0 + 12 Combine like terms: 0 + 12 = 12 4x = 12 Divide each side by '4'. x = 3 Simplifying x = 3
| 3x-12+x=4 | | 10.2x+0.8=22 | | 34(x-2)=2 | | f(n)=3f(n-1)-1 | | (((1300000-x)/2)/1300000)=0.1 | | 15=23-4m | | 14x+11=4x+11 | | h(-3)=3x-3 | | =11+0.9(y-10) | | 25+x=78 | | 2x+7=3x-(6x-2) | | 2(p+5)-3p=14 | | X+X+1(X+2)=160 | | 4x+-3x+-5x= | | -5y+3-4y=2 | | 2.14-0.3x=2.24 | | 1/2=x1/4 | | 75000=x(x+3) | | 5(x+4)=3[x-(4-x)] | | 15x+30=15x-90 | | -2.9=f+4.3 | | 2x-12y+5=0 | | sinx+14.87cosx=1.5 | | 0.5x+0.08=0.13 | | 3(g-2)+2=5g-7-2g | | 12x-(3x-9)=27 | | (x-2)(x-2)(x+3i)(x-3i)=0 | | 175000=x(x+3) | | 7x+10000=5x+14000 | | 7x+10000=10x+6000 | | f(-4)=8 | | (-5(x=6)/3)=10 |